Effect of Protein Intake on Visceral Abdominal Fat and Metabolic Biomarkers in Older Men With Functional Limitations: Results From a Randomized Clinical Trial. (8th January 2021) - Huang, Grace; Pencina, Karol; Li, Zhuoying; Apovian, Caroline M; Travison, Thomas G; Storer, Thomas W; Gagliano-Jucá, Thiago; Basaria, Shehzad; Bhasin, Shalender
Abstract: Background: It remains controversial whether high protein diets improve cardiometabolic profile. We investigated whether increasing protein intake to 1.3 g/kg/day in functionally limited older adults with usual protein intake ≤RDA (0.8 g/kg/day) improves visceral fat accumulation and serum cardiovascular risk markers more than the recommended daily allowance (RDA). Methods: The Optimizing Protein Intake in Older Men Trial was a placebo-controlled, randomized trial in which 92 functionally limited men, ≥65 years, with usual protein intake ≤RDA were randomized for 6 months to: 0.8 g/kg/day protein plus placebo; 1.3 g/kg/day protein plus placebo; 0.8 g/kg/day protein plus testosterone enanthate 100 mg weekly; or 1.3 g/kg/day protein plus testosterone enanthate 100 mg weekly. In this substudy, metabolic and inflammatory serum markers were measured in 77 men, and visceral adipose tissue (VAT) was assessed using dual-energy x-ray absorptiometry in 56 men. Results: Treatment groups were similar in their baseline characteristics. Randomization to 1.3 g/kg/day protein group was associated with greater reduction in VAT compared to 0.8 g/kg/day group (between-group difference: −17.3 cm 2, 95% confidence interval [CI]: −29.7 to −4.8 cm 2, p = .008), regardless of whether they received testosterone or placebo. Changes in fasting glucose, fasting insulin, HOMA-IR, leptin, adiponectin, IL-6, and hs-CRP did not differ between the 0.8 versus 1.3 g/kg/day protein groups regardless of testosterone use. Conclusions: Protein intake >RDA decreased VAT in functionally limited older men but did not improve cardiovascular disease risk markers. Clinical Trials Registration Number: NCT01275365